2006
DOI: 10.1523/jneurosci.4658-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Complex Spike Activity of Purkinje Cells in the Oculomotor Vermis during Behavioral Adaptation of Monkey Saccades

Abstract: Throughout life, the oculomotor system can correct itself when saccadic eye movements become inaccurate. This adaptation mechanism can be engaged in the laboratory by displacing the target when the saccade toward it is in flight. Forward and backward target displacements cause gradual increases and decreases in saccade amplitude, respectively. Equipped with this paradigm, we asked whether Purkinje cells (P-cells) in the vermis of the oculomotor cerebellum, lobules VIc and VII, changed their complex spike (CS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
118
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 36 publications
8
118
1
2
Order By: Relevance
“…In our previous study (Soetedjo and Fuchs 2006), we reported that the CS activity in the interval between the end of dysmetric primary saccades and the onset of the subsequent corrective saccades either increased or decreased during saccade adaptation. Because of the limitations of the behavioral paradigm used in that experiment, we could only determine whether the CS activity preferred left-or rightward error directions, and we also were unable to control error size systematically.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our previous study (Soetedjo and Fuchs 2006), we reported that the CS activity in the interval between the end of dysmetric primary saccades and the onset of the subsequent corrective saccades either increased or decreased during saccade adaptation. Because of the limitations of the behavioral paradigm used in that experiment, we could only determine whether the CS activity preferred left-or rightward error directions, and we also were unable to control error size systematically.…”
Section: Introductionmentioning
confidence: 82%
“…We surgically implanted a scleral search coil on one eye to measure eye position with an electromagnetic technique (Fuchs and Robinson 1966;Robinson 1963) and stabilization lugs on the skull to prevent head movements. Once the monkeys had recovered from the surgery, they were placed in a dimly lit room and trained to make saccades to a jumping target spot that moved every 1-1.5 s and to fixate the target for from 0.4 to 1s, not including their reaction times, in return for an applesauce reward (Soetedjo and Fuchs 2006). The target was either the image of a red laser spot reflected from two mirror galvanometers (target diameter ϭ 0.4°) onto a cylindrical drum surrounding the monkey or one of many light emitting diodes that were attached to a sphere facing the monkey.…”
Section: General Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The deeper layers of the SC are connected to the medioposterior cerebellum (caudal fastigial nucleus and oculomotor vermis; Ohtsuka and Noda 1990) via nucleus reticularis tegmenti pontis (NRTP; May et al 1990;Ohtsuka and Noda 1990) and dorsal lateral pontine nucleus (Thier and Mock 2005). Lesions to the medioposterior cerebellum impair rapid saccade amplitude adaptation during the McLaughlin task (Barash et al 1999;Robinson et al 2002;Takagi et al 2000) and the burst metrics of neurons in NRTP (Takeichi et al 2005), caudal fastigial nucleus (Inaba et al 2003;Scudder and McGee 2003), and oculomotor vermis (Catz et al 2005(Catz et al , 2008Soetedjo and Fuchs 2006) are altered along with saccade amplitude during head-restrained saccadic adaptation. Future studies are required to classify the types of motor command signals (gaze, eye, or head) represented at each level of this circuit prior to describing modifications to these signals during gaze adaptation using the McLaughlin task.…”
Section: Physiological Implicationsmentioning
confidence: 99%